Ozonated water and Food Industry: Antimicrobial evaluation in the disinfection of rainbow trout (Oncorhynchus mykiss) fillets. - Pasapera-Campos, Sandra Eloisa (2024)
Hydrobiological products are highly perishable, which is why this research was carried out Hydrobiological products are highly perishable, which is why this research was carried out with the objective of evaluating the microbial load in the disinfection of rainbow trout (Oncorhynchus mykiss) fillets concerning Staphylococcus aureus, aerobic mesophiles, Salmonella sp. and Escherichia coli, submerging at different times (30, 60 and 90 s) and concentrations (0.5, 1.5 and 2.5 ppm). Microbiological analysis was performed on days 1, 8, 15, and 22 of refrigeration (4 °C), controlling pH according to AOAC 981.12 (1990). The experimental design was 3O x 3T factorial, with three replicates per treatment. R Project was used to perform ANOVA and Tukey's tests. The results revealed that treatment with ozonated water, especially using 2.5 ppm ozone and 30 seconds of immersion (O3T1), showed a significant antimicrobial effect against Staphylococcus aureus, maintained the levels of aerobic mesophiles below the minimum limit and prevented the development of Salmonella sp per 25 g of fillet and Escherichia coli per 10 g of fillet. In conclusion, the results demonstrate that the use of ozone plays a crucial role in both stabilizing pH and significantly decreasing the microbial loads examined.